Syntactic And Punctuation Features of Newspaper Headlines As A Possibility Of Pragmatic Influence Expression Possibilities Of The Syntax Of Newspaper Headlines (Open Herald: Periodical of Methodical Research, 2024)
Newspaper headlines are an important way to communicate news and capture readers' attention. These concise and attention-grabbing formulations not only inform but also shape the readers' perception of the following news. To understand their pragmatic influence on readers, it is important to understand the syntax and punctuation features of newspaper headlines. In this article, we consider the possibilities that newspaper headline syntax offers for expressing pragmatic influence. Syntactic and punctuation features play a fundamental role in capturing the essence of a message within the space limitations of a headline. Careful arrangement of words and use of punctuation allows journalists to convey important information effectively and capture readers' interest. By examining these characteristics, we can uncover the conscious choices that headline writers make to influence readers' interpretations and reactions to the news.